Penerapan Khiyar pada Pengembalian Barang Dalam Transaksi Jual Beli Pakaian Grosir Di Pasar Komplek WTC Jambi - Sari, Ani Mutiara; Pangiuk, Ambok; Baining, Mellya Embun (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2022)
This research aims to determine the application of khiyar in the return of goods in buying and selling clothes at the Jambi WTC complex market. This study uses qualitative analysis methods, where primary data is obtained from interviews and secondary data is obtained from documentation. The place in this study is the WTC Jambi shop-house complex market and the actors in this study are traders and buyers in the WTC Jambi shop-house complex market. The results of the study are as follows. (1) The application of khiyar on the return of goods at the Jambi WTC complex market has been carried out even though there is still need for improvement or it is not maximized besides that the majority do not recognize the term